Formulation of Zolmitriptan Nanosponges Embedded in Fast-Dissolving Sublingual Films: A 3² Factorial Optimization Study - Adil Patel; Nidhi Joshi; Chirag Parmar; Nidhi Joshi (The Bioscan, 2025)
The Zolmitriptan is a serotonin (5- HT1) agonist used for the treatment of migraine with or without aura. The half-life of Zolmitriptan is 2.5 to 3 hr, the absolute oral bioavailability is about 40 to 50%. Hence the main objective of the study was to formulate & develop zolmitriptan loaded nanosponge based sublingual film to achieve a better permeability and further improving the bioavailability of the drug. Zolmitriptan nanosponge (ZMT-Ns) were prepared by emulsion solvent diffusion method and then encapsulated into the films by solvent casting method. 32 factorial design applied to analyses the influence of independent variables, concentration of polymer polyvinylalcohol, EC, on the responses for dependent variables, particle size, Entrapment Efficiency and PDI which were found to be 373nm, 93.23%,0.389. The drug release from nanosponges was found to extended up to 8h. Morphological characters were identified by scanning electron microscopy. Solid state characteristic of the drug in the formulation was evaluated by X-ray diffraction. FDSFs were evaluated for their disintegration time, weight variation, thickness, drug content, and surface ph. Stability studies were performed at 40 ± 2 °C/75 ± 5% RH. These results indicated that the ZMT-Ns FDSFs could be a promising delivery system to enhance the permeability and further improving the bioavailability of the drug. KEYWORDS Zolmitriptan, Migraine, Nanosponge, Sublingual Film, Bioavailability, Emulsion Solvent Diffusion, Poly Vinayl Alcohol